Microbiological characterization of protected designation of origin Serra da Estrela cheese - Rocha, Rui (2023)
Serra da Estrela is the oldest and most recognizable traditional protected designation of origin (PDO) cheese from Portugal. It has been extensively studied over the years, but the latest microbial characterization is 20 years old. Hence, this work aimed to perform an updated characterization of Serra da Estrela PDO cheeses and raw materials. Our analysis showed that lactic acid bacteria content on Serra da Estrela cheeses exceeded 8.8 log CFUsg−1 , in all analyzed samples, with lactococci, lactobacilli and Leuconostoc spp. predominating over enterococci strains. Moreover, lactococci and lactobacilli abundance increased across the production season, while enterococci dropped considerably in late manufactures. Lastly, Leuconostoc spp. content remained unchanged in all analyzed periods. A correspondence analysis showed that L. paracasei, L. lactis, E. durans, E. faecium and L. mesenteroides are transversal in Serra da Estrela cheese manufacturing and were closely associated with milk, curd and cheese matrices. Additionally, L. casei, L. plantarum and L. curvatus were specifically associated with cheese matrices, possibly active during ripening and contributing for the development of these cheeses’ organoleptic characteristics.